APLIKASI PENGINDERAAN JAUH UNTUK PERENCANAAN TATA RUANG WILAYAH PESISIR DAN PULAU- PULAU KECIL - Bitta Pigawati (TEKNIK, 2012)
Our beloved country, Indonesia has planty natural resources both in the sea and it the land. It can be seen to thefact that Indonesia is and archipelago country which has thousands islands. Most of our area is surrounded bythe sea that provides foot resources, mining resources, mineral, energy, and tourism place. In short It can besaid that coastal area is not only as living resources for people surrounding but also supporting our nationalsocial and economic development. In order to use the resources optimally and efficienly it need not only a goodplan but also an integrated management.A plan has become a part of everyone’s life. It has been used since people realized they need it to solve aproblem. People often get confused between planning and actuating their daily activities, so it needs acomprehensive understanding about what plan means. Plan is a process, process of thinking and actuating it dosomething). Planning acts as an intervening variable between knowledge and action. The essence of planning ispreventative rather than remedial.Spatial planning is a process of area planning system. Master plan of small islands is one of the detail masterplan. Coastal area is a border area between land and sea. The coastal area management is a process to plan, touse, to supervise, and to control the coastal area as well as coastal resources. Master plan is set into some formsbased on its scale or its area to coverage, its detail level, and its focus and attention. Spatial plan is well knownas master plan RTRWN, RTRWP, TRTW Kota/ Kabupaten to design the three master plans takes three phases,they are data compilation, analysis and planning; further more, the three phases are always completed withsome maps to give illustration and comprehensive understanding about phenomena spatially. The integratedcoastal resources management and planning need information about what potention can be developed as well aswhat problems come up.Remote sensing is an observation method or spatial elements measurement of earth’s surface. This effective andefficient method really supports any activities which use spatial approach. Remote sensing data really suit forcoastal area management and planning research due to the large area to investigate and to reach. The use ofremote sensing data for spatial plan has a function for not only completing the existing data but also providingthe newest information. Considering and area developed rapidly it needs available data to monitor and toevaluate the implementation of a master plan. Some problems emerged as a result of using remote sensing dataare such as; limited budged and limited human resources who are able to use remote sensing.